Ihsan as Ethical Virtue for Neighborhood Community - Malik, Mohammad Manzoor (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This study demonstrates that there is a need of addressing neighborhood relationships in contemporary times. And in this regard, a position from Islam is considered in which neighborly relationships are based on Quranic ethical virtue ihsan i.e., doing good to others. The word neighbor in the Quran and Hadith is a general term that is not discriminatory. It includes Muslims and non-Muslims. This insight is very useful for building relationships in multicultural and multireligious communities for harmony and peace. To locate a neighbor, though there are jurisprudential opinions, leaving it to its customary use is preferred in this study. The neighborhood rights and duties are given in detail. And it is also demonstrated that those prophetic narrations in which harming neighbors or committing sins against them is considered as the consequence of the absence of faith in fact show the disgust of such sinful acts; therefore, a sinful Muslim is not considered as a non-believer. The harm is especially illustrated with infringing the privacy of a neighbor. It has been shown that Ihsan includes ethically both non-maleficence and beneficence. Most of the prophetic traditions can be classified under these two categories. In addition to this, it is also shown that the neighborhood relations in Islam also include the Golden Rule which is all-encompassing and in principle exhaustive. Keywords: Neighbor, Islam, Golden Rule, Ihsan, beneficence